CAPITAL STRUCTURE IMMUNIZE OR INFECT VALUE OF THE FIRM - Fernando, A.A.J. (My University, 2016)
Attached

The study examines the capital structure that envisages firm immunize or infects the firm value, firm tend to prefer risk minimum and higher return structure, and the value of the firm differs greatly across the industries. Finance strategy is equated widely with crafting and maintaining a profitable fit between the finance need and the disbursement of firm investment. Capital structure and value o f the firm is controversial and famous unsolved issues in the field of finance. Still there is inconclusive in any research circumstance. But firm decision making folder is arguable and challenging against capital structure decisions and achieving the optimal capital structure is one o f the most vital and important issues. At the same time capital structure decisions plays important role in the field of finance for saving firm ’s stability, profitability and strength. Stability, profitability and strength are major factors for any firm. In order to achieve three successive factors, a manger o f a firm improving business process often is required to make capital structure related decisions in a proper order. This study examines optimal capital structure where value of the firm enriches its optimum. Study highlight by observing that if external sources offinance are costly to firms than internally generated funds., there will typically be a benefit to investment which adds value to the extent that it helps ensure that a firm has sufficient internal funds available to take advantage of attractive investment opportunities. Study delineates how these financing strategies should depend on such factors as shocks or shift to investment and financing opportunities which leads to maximize the value of the firm.
Keywords: Value of the firm; Optimal Capital Structure; Stability; profitability; strength